Gamma-ray and neutrino emission from misaligned microquasars - Romero, Gustavo Esteban (2005)
Microquasars are accreting X-ray binary systems with non-thermal radio jets. In some of these systems the jet is expected to be strongly misaligned with the perpendicular to the orbital plane. If the donor star is an early-type star, the jet could collide with the stellar wind producing a standing shock between the compact object and the stellar surface. Relativistic particles injected by the jet can be re-accelerated and isotropized at the colliding region. If the jet has hadronic content, TeV protons will diffuse into the inner, dense wind leading to gamma-ray and neutrino production from interactions with the matter of the wind. In the case of very powerful jets, the wind pressure can be overbalanced and the jet might impact directly onto the stellar surface. We present estimates of the gamma-ray and neutrino luminosities for different sets of parameters in these scenarios and we briefly discuss the effects of this radiation on the donor star and its detectability with current instruments.